2022
DOI: 10.1002/alz.12546
|View full text |Cite
|
Sign up to set email alerts
|

APP accumulates with presynaptic proteins around amyloid plaques: A role for presynaptic mechanisms in Alzheimer's disease?

Abstract: In Alzheimer's disease (AD), the distribution of the amyloid precursor protein (APP) and its fragments other than amyloid beta, has not been fully characterized. Here, we investigate the distribution of APP and its fragments in human AD brain samples and in mouse models of AD in reference to its proteases, synaptic proteins, and histopathological features characteristic of the AD brain, by combining an extensive set of histological and analytical tools. We report that the prominent somatic distribution of APP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 84 publications
3
7
0
Order By: Relevance
“…In line with these findings, we here provide evidence that presynaptic APP -which might promote localized actions of Aβ at presynaptic sites -is essential to restrain excitatory synaptic transmission at medial perforant path synapses on dentate granule cells. These findings support recent evidence on the role of presynapses in the pathogenesis of Alzheimer's disease (Barthet and Mulle, 2020;Jorda-Siquier et al, 2022). In support of a restraining effect of APP and its proteolytic cleavage products, we here show at the level of connected pairs of neurons that presynaptic APP controls the efficacy and strength of perforant path synapses.…”
Section: Discussionsupporting
confidence: 92%
“…In line with these findings, we here provide evidence that presynaptic APP -which might promote localized actions of Aβ at presynaptic sites -is essential to restrain excitatory synaptic transmission at medial perforant path synapses on dentate granule cells. These findings support recent evidence on the role of presynapses in the pathogenesis of Alzheimer's disease (Barthet and Mulle, 2020;Jorda-Siquier et al, 2022). In support of a restraining effect of APP and its proteolytic cleavage products, we here show at the level of connected pairs of neurons that presynaptic APP controls the efficacy and strength of perforant path synapses.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings fuel the hypothesis that impairments in axonal transport underlie the axonal pathology and pathogenesis of AD 1,2,37,38 . Genetic manipulation of APP 24 , its proteolytic machinery 22,25,39 and of all other major proteins linked to AD including tau 40,41 and ApoE 42 in flies and mice produces invariably axonal pathology reminiscent of the one described in molecular motor deficiencies 43 .…”
Section: Discussionsupporting
confidence: 85%
“…Extracellular amyloid plaque is a pathological hallmark of AD, with Aβ as its major component [ 3 , 35 ]. Compared to Aβ40, Aβ42 is more prone to aggregation, owning to its increased hydrophobicity of expanded C terminus [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…BACE1 inhibitor could reduce Aβ generation in AD mice brains and AD patients’ brains [ 41 ]. In particular, both BACE1 and PSEN1 are found within amyloid plaque of human AD brain [ 35 ]. In our research, increased PSEN1 and decreased BACE1 were observed in N2a-hAPP cells treated with 2JY-OBZ4.…”
Section: Discussionmentioning
confidence: 99%